MASIH PERLUKAH SASTRA DI ERA INDUSTRI ? - Eriyanti, Ribut Wahyu (Jurnal Bestari, 1992)
Learning literature will remind us on the process of Indonesia's physical revolution. Reading through Chairil Anwar's poem entitled "Diponegoro", for instance, could make Indonesian's spirit of struggle rise to get away colonialism that intended to maintain Indonesia as colonialized country. The master piece of literature, it is admitted or not, has contributed Indonesia people to combat againts the colonialisation and has made them independent. Literature as a great "mirror" of a certain nation may reflect the culture of nation itself. Now we live i the industrial age which all aspects must be considered by logical power objectively. Although we live in it, however, we still need other master piece of literature in order to increase our humanity.